Phylogenetic and Functional Diversity of Fleshy-Fruited Plants Are Positively Associated with Seedling Diversity in a Tropical Montane Forest - Muñoz, Marcia C.; Schaefer, H. Martin; Böhning-Gaese, Katrin; Neuschulz, Eike Lena; Schleuning, Matthias (Frontiers in Ecology and Evolution, 2017)
Mutualistic interactions between plants and animals can affect both plant and animal communities, and potentially leave imprints on plant demography. Yet, no study has simultaneously tested how trait variation in plant resources shapes the diversity of animal consumers, and how these interactions influence seedling recruitment. Here, we analyzed whether i) phylogenetic diversity and functional diversity of fruiting plants were correlated with the corresponding diversity of frugivorous birds, and ii) whether phylogenetic diversity and functional identity of plant and bird communities influenced the corresponding diversity and identity of seedling communities. We recorded mutualistic interactions between fleshy-fruited plants and frugivorous birds and seedling communities in ten plots along an elevational gradient in the Colombian Andes. We built a phylogeny for plants/seedlings and birds and measured relevant morphological plant and bird traits that influence plant-bird interactions and seedling recruitment. We found that phylogenetic diversity and functional diversity of frugivorous birds were positively associated with the corresponding diversities of fruiting plants, consistent with a bottom-up effect of plants on birds. Moreover, the phylogenetic diversity of seedlings was related to the phylogenetic diversity of plants, but was unrelated to the phylogenetic diversity of frugivorous birds, suggesting that top-down effects of animals on seedlings were weak. Mean seed mass of seedling communities was positively associated with the mean fruit mass of plants, but was not associated with the mean avian body mass in the frugivore communities. Our study shows that variation in the traits of fleshy-fruited plants was associated with the diversity of frugivorous birds and affected the future trajectory of seedling recruitment, whereas the morphological traits of animal seed dispersers were unrelated to the phylogenetic and functional structure of seedling communities. These findings suggest that bottom-up effects are more important than top-down effects for seed-dispersal interactions and seedling recruitment in diverse tropical communities.